2008
DOI: 10.1007/s00256-008-0478-8
|View full text |Cite
|
Sign up to set email alerts
|

Fast T2 mapping of the patellar articular cartilage with gradient and spin-echo magnetic resonance imaging at 1.5 T: validation and initial clinical experience in patients with osteoarthritis

Abstract: Fast T2 mapping of the patellar articular cartilage can be performed with GRASE within a third of the time of that of standard sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Our current study in some ways is similar to theirs, although a valid comparison cannot be undertaken due to major differences in the MRI technique (an ultra-high-field whole-body system at 7T in the Welsch et al (18) study vs. a standard clinical 1.5T scanner in ours). In another study by Quaia et al (19) a technique of fast T 2 mapping was reported and T 2 values derived from MR spectroscopy were compared to turbo spin-echo (TSE) and gradient-spin-echo (GRASE) MRI-derived T 2 values at 1.5T for patellar cartilage evaluation in 35 patients. Their study demonstrated a good correlation between T 2 values using GRASE and TSE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our current study in some ways is similar to theirs, although a valid comparison cannot be undertaken due to major differences in the MRI technique (an ultra-high-field whole-body system at 7T in the Welsch et al (18) study vs. a standard clinical 1.5T scanner in ours). In another study by Quaia et al (19) a technique of fast T 2 mapping was reported and T 2 values derived from MR spectroscopy were compared to turbo spin-echo (TSE) and gradient-spin-echo (GRASE) MRI-derived T 2 values at 1.5T for patellar cartilage evaluation in 35 patients. Their study demonstrated a good correlation between T 2 values using GRASE and TSE.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI examination consisted of two parts (MRI precontrast, MRI postcontrast). The first part was the precontrast protocol that included a 3D GRE sequence (multiecho data image combination [MEDIC]) with six echoes in order to assess a T* 2 map: repetition time (TR) ϭ ϳ28 ms, echo time (TE) ϭ 4.68 ms, 8.82 ms, 12.96 ms, 17.10 ms, 21.24 ms, and 25.38 ms, flip angle (FA) ϭ 25, bandwidth (BW) ϭ 260 kHz, number of excitations (NEX) ϭ 3, slice thickness ϭ 0.78 mm, slice gap ϭ 100%, field-of-view (FOV) ϭ 200 mm, matrix size ϭ 256 ϫ 256, number of sections ϭ 96, and TA ϭ 8 min 3 s. T* 2 maps were assessed inline using a nonlinear least squares fitting routine (19). In the second part involving indirect MR arthrography and dGEMRIC, 0.4 ml/kg body weight of gadolinium contrast agent (Magnevist; Schering AG, Berlin, Germany) was administered intravenously.…”
Section: Mrimentioning
confidence: 99%
“…Quaia et al [8] found that gradient and spin-echo sequence (GRASE) provided T2 values slightly lower than those obtained by TSE sequence in most patients (mean difference ± SD, 1.81 ± 3.63 ms). This difference may be due to the presence of T2* decay in the GRASE sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The available mappings for cartilage tissue are T1 mapping, T2 mapping and T2-star (T2*) mapping but the most commonly used is T2 mapping which can evaluate the status of the cartilage matrix and identify biochemical changes associated with the early stages of OA [8,9]. Several studies have demonstrated that T2 mapping is useful for the detection of early stages of matrix degeneration [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of the proposed approach was assessed on 35 patients (21 males and 14 females) with moderate degree of patellar osteoarthritis. (Quaia et al, 2008).…”
Section: Fast T2 Mapping Of the Patellar Articular Cartilagementioning
confidence: 99%